Two decades of ecohydraulics: trends of an emerging interdiscipline. Issue 1 (2nd July 2016) - Casas-Mulet, Roser; King, Elise; Hoogeveen, Doris; Duong, Long; Lakhanpal, Garima; Baldwin, Timothy; Stewardson, Michael J.; Webb, J. Angus
ABSTRACT: We assessed how the emerging field of ecohydraulics research has changed over two decades by examining the proceedings of the biennial International Symposium on Ecohydraulics. By using Natural Language Processing (NLP) in word usage, this paper provides a deep analysis of a longitudinal dataset and enables us to test more detailed questions than previous snapshots of the ecohydraulics literature. We formulated three main hypotheses related to the degree of multidisciplinarity, interdisciplinarity and transdisciplinarity within ecohydraulics. We investigated temporal changes in author affiliation patterns and identified dominant topics of research. The total number of proceeding papers has increased over time and the field is becoming increasingly global. This and the identification of 10 distinctive macro-topics suggest well-developed multidisciplinarity in ecohydraulics. There has been reasonable stability in individual topics across time, except for 11 (out of 51) significant trends within the macro-topics of Fish responses, Hydraulic modelling, Water quality, Physical habitat modelling and Social responses, suggesting some increase in interdisciplinarity. The proportion of practitioners collaborating with researchers has surprisingly not changed greatly over time, indicating ecohydraulics has been transdisciplinary to some extent from its inception. Our results arguably provide an opportunity to better integrate fundamental understanding into practical applications in water management.